Strategi Perencanaan Standarisasi Delapan Standar Nasional Pendidikan (SNP) di SDN Pamulang Indah - Elis Lisyawati; Jamilah Muryati; Aris Munandar; Naufal Hilmizen; Khairunnisa; Edi Ruslani; Ade Ripai; Iim Wasliman; Supyan Sauri (EduInovasi: Journal of Basic Educational Studies, 2024)
It can be stated that when designing a plan for a primary school, it is important to ensure that the plan is in line with the 8 National Education Standards (NES). These standards provide a solid performance framework for improving the quality of education, ensuring every aspect of education functions properly. The research method uses a descriptive qualitative approach, with interview techniques, observation and supported by documentation for data collection. The analysis through the data visualisation approach produced by Atlas.ti 9 describes Pamulang Indah Primary School as a pioneer of excellence in education. The school's unwavering commitment to implementing the 8 National Education Standards (SNP) is evident in its comprehensive and structured approach. By prioritising quality education for all. SDN Pamulang Indah has made significant progress in fulfilling most of the 8 National Education Standards (SNP), although there are still shortcomings that need attention, especially in the Financing Standard. The high dependence on APBN and BOS funds has caused some student activities to be hampered when these funds are insufficient or disbursed late. This points to the need for strategic measures to find alternative sources of funding to ensure the smooth running of all educational activities. To overcome the dependence on APBN and BOS funds, SDN Pamulang Indah can seek to diversify funding sources by collaborating with the private sector, raising funds through community activities or applying for assistance from donor agencies. With these measures, the school can be more financially independent and ensure the smooth running of all educational activities, including extra-curricular activities and facility development, without having to rely too heavily on the government budget.